2021
DOI: 10.4196/kjpp.2021.25.4.321
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effects of lutein against vancomycin-induced acute renal injury in mice via upregulation of peroxisome proliferator-activated receptor gamma/nuclear factor erythroid 2-related factor 2 and inhibition nuclear factor-kappaB/caspase 3

Abstract: Kidneys are the main excretory organ for many drugs, and could easily be exposed to toxins. Nephrotoxicity has been reported to contribute to approximately 8%-40% of all cases of acute renal injury. Since its introduction, vancomycin, a glycopeptide antibiotic often used as the last line of defense against drug resistant gram-positive bacteria, has been associated with acute renal injury [1,2]. Vancomycin is commonly used to treat hospitalacquired methicillin-resistant Staphylococcus aureus (MRSA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Lutein treatment blocked the high glucose-mediated elevation of intracellular reactive oxygen species, PCO, and MDA content in ARPE-19 cells [ 25 ]. Lutein protected against vancomycin-induced renal injury by decreasing MDA, PCO, and related inflammatory and apoptotic signal pathways [ 26 ]. The decreases in the oxidative terminal products of biological macromolecules by lutein in the present study and the literature demonstrated the protective effect of lutein in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Lutein treatment blocked the high glucose-mediated elevation of intracellular reactive oxygen species, PCO, and MDA content in ARPE-19 cells [ 25 ]. Lutein protected against vancomycin-induced renal injury by decreasing MDA, PCO, and related inflammatory and apoptotic signal pathways [ 26 ]. The decreases in the oxidative terminal products of biological macromolecules by lutein in the present study and the literature demonstrated the protective effect of lutein in the body.…”
Section: Discussionmentioning
confidence: 99%
“…These samples were homogenized in phosphate-buffered saline in a ratio of 1:10 (w/v) homogenates and then centrifuged at 13,000× g (4 • C) for 30 min; the supernatant was then collected to determine the levels of MDA, SOD, and GSH. The levels of MDA, as a marker for lipid peroxidation, were determined using the thiobarbituric-acid-reactive substances method by determining the levels of thiobarbituric-acid-reactive substances, as earlier described by Emeka et al [43]. A phosphoric acid solution (1%) and a measured volume of thiobarbituric acid were added to each sample homogenate, which was then incubated at 95 • C for 1 h. The concentration of the subsequent thiobarbituric-acid-reactive substances was then measured spectrophotometrically at 535 nm.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…Dietary lutein supplementation (50 mg/kg body weight) inhibits LPS-induced elevation of splenic levels of IL-1 and PPAR-γ in chickens (22). Additionally, lutein protects against vancomycin-induced renal injury by upregulating PPAR-γ (23).…”
Section: Introductionmentioning
confidence: 99%